Novel single‐operator through‐the‐scope traction device for endoscopic submucosal dissection: Outcomes of a multicenter randomized pilot ex‐vivo study in trainees with limited endoscopic submucosal dissection experience (with video). Issue 1 (10th October 2022) - Yang, Dennis; Aihara, Hiroyuki; Hasan, Muhammad K.; Simsek, Cem; Khan, Hafiz; Brar, Tony S.; Gorrepati, Venkata S.; Forde, Justin J.; Kadkhodayan, Kambiz; Arain, Mustafa A.; Draganov, Peter V.
Abstract: Objectives: Endoscopic submucosal dissection is a technically demanding procedure. The pilot study aimed to prospectively evaluate the efficacy and safety of a novel single‐operator through‐the‐scope dynamic traction device among trainees with limited endoscopic submucosal dissection (ESD) experience. Methods: Randomized, controlled, pilot study comparing traction‐assisted ESD (T‐ESD) versus conventional ESD (C‐ESD) in an ex‐vivo porcine stomach model. Trainees were randomized to group 1 (T‐ESD followed by C‐ESD) and group 2 (C‐ESD followed by T‐ESD). Lesions were created on the gravity‐dependent area of the stomachs. The primary outcome was submucosal dissection speed. Secondary outcomes included differences in en‐bloc resection, adverse events, and workload, assessed by the National Aeronautical and Space Administration Task Load Index (NASA‐TLX). Results: Five trainees performed two T‐ESD and two C‐ESD each, for a total of 20 procedures. Submucosal dissection speed was significantly faster in the T‐ESD group compared to the C‐ESD group (43.32 ± 22.61 vs. 24.19 ± 15.86 mm 2 /min; p = 0.042). En‐bloc resection was achieved in 60% with T‐ESD and 70% with C‐ESD ( p = 1.00). The muscle injury rate was higher in the C‐ESD group (50% vs. 10%; p = 0.21) with 1 perforation reported with C‐ESD and none with T‐ESD. NASA‐TLX physical demand was lower with T‐ESD compared to C‐ESD (4.5 ± 2.17 vs. 6.9 ± 2.50; p = 0.03). Conclusion: T‐ESD resulted in faster submucosal dissection and less physical demand when compared to C‐ESD, as performed by trainees in an ex‐vivo gravity‐dependent model. Future studies are needed to assess its role in human ESD cases.